COMPARATIVE ANALYSIS AND EVALUATION OF PHYSICAL AND MECHANICAL PROPERTIES OF A-SILICONE FLEXIBLE CONSTRUCTION MATERIALS - I.V. Yanishen; S.A. German (Український стоматологічний альманах)
The aim of the study was to investigate the physical and mechanical properties of A-silicone materials «PM-S», «PM-S Extra» and «UfI Gel P» (Voco) in a comparative perspective.